Interdisciplinary Approach on Contemporary Islam in Indonesia - Rusli, Muh. (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2023)
The interdisciplinary approach in Islamic studies has gained importance in contemporary Indonesia. The importance is mainly due to its socio-political issues, historical and cultural factors, and educational limitations. This research lays out the theoretical foundations of an interdisciplinary approach and explains why it is superior to more conventional methods. The primary purpose of this research is to analyse the benefits and drawbacks of an integrated strategy when studying Islam, focusing on Indonesia. In this research, the author argues that conventional methods fall short because of the complexity inherent in accounting for the myriad social, political, and cultural aspects that shape Islamic praxis. The finding of this research suggests that an interdisciplinary approach necessitates the merging of fields like sociology, anthropology, psychology, and history, as well as the promotion of novel partnerships and collaborations, in order to produce novel and original insights. It has ramifications for both study and teaching in Islamic studies as a methodology with the potential to enhance our understanding of the present Islamic world, Islamic cultural practices, and their historical origins. Insight into the Islamic world has improved, as has the standard of Islamic education, and societal tolerance and peace have blossomed due to these efforts. Future interdisciplinary applications in Islamic studies and their potential and promise are discussed. By encouraging collaboration and partnership across disciplines, an interdisciplinary approach can lead to a richer and more complex understanding of the Islamic world. Islamic studies benefit from an interdisciplinary strategy since it encourages more innovative and critical thinking. ملخّص اكتسب النهج متعدد التخصصات في الدراسات الإسلامية أهمية في إندونيسيا المعاصرة بسبب قضاياها الاجتماعية والسياسية، والعوامل التاريخية والثقافية، والقيود التعليمية. توضح هذه المقالة الأسس النظرية لنهج متعدد التخصصات وتشرح سبب تفوقه على الأساليب التقليدية. الغرض الأساسي من هذا المقال هو تحليل فوائد وعيوب الإستراتيجية المتكاملة عند دراسة الإسلام، مع التركيز على إندونيسيا. في هذه الدراسة، نرى أن الأساليب التقليدية غير كافية بسبب التعقيد الكامن في مراعاة الجوانب الاجتماعية والسياسية والثقافية التي لا تعد ولا تحصى والتي تشكل الممارسة الإسلامية. تشير نتائج هذه المقالة إلى أن النهج متعدد التخصصات يستلزم دمج مجالات مثل علم الاجتماع والأنثروبولوجيا وعلم النفس والتاريخ، بالإضافة إلى تعزيز الشراكات والتعاون الجديد، من أجل إنتاج رؤى جديدة ومبتكرة. وله تداعيات على كل من الدراسة والتدريس في الدراسات الإسلامية كمنهجية لديها القدرة على تعزيز فهمنا للعالم الإسلامي الحالي، والممارسات الثقافية الإسلامية، وأصولها التاريخية. لقد تحسنت الرؤية للعالم الإسلامي، كما تحسن مستوى التعليم الإسلامي، وازدهر التسامح المجتمعي والسلام بفضل هذه الجهود. وتناقش التطبيقات المستقبلية متعددة التخصصات في الدراسات الإسلامية وإمكاناتها ووعودها. ومن خلال تشجيع التعاون والشراكة عبر التخصصات، يمكن أن يؤدي النهج متعدد التخصصات إلى فهم أكثر ثراءً وتعقيدًا للعالم الإسلامي. تستفيد الدراسات الإسلامية من استراتيجية متعددة التخصصات لأنها تشجع المزيد من التفكير الابتكاري والنقدي. الدراسات الإسلامية؛ دراسة متعددة التخصصات؛ نهج متعدد التخصصات؛ إندونيسيا Abstrak Pendekatan interdisipliner dalam studi Islam menjadi penting di Indonesia terkini. Pentingnya pendekatan ini karena masalah sosial-politik, faktor sejarah dan budaya, dan keterbatasan pendidikan. Penelitian ini memaparkan landasan teoretis pendekatan interdisipliner dan menjelaskan mengapa pendekatan ini lebih unggul daripada metode konvensional. Dalam penelitian ini, penulis berpendapat bahwa metode konvensional gagal karena kompleksitas yang melekat dalam memperhitungkan berbagai aspek sosial, politik, dan budaya yang membentuk praksis Islam. Temuan penelitian ini menunjukkan bahwa pendekatan interdisipliner memerlukan penggabungan bidang-bidang seperti sosiologi, antropologi, psikologi, dan sejarah, serta promosi kemitraan dan kolaborasi baru untuk menghasilkan wawasan baru dan orisinal. Hal ini mempunyai konsekuensi bagi studi dan pengajaran studi Islam sebagai metodologi yang berpotensi meningkatkan pemahaman kita tentang dunia Islam saat ini, praktik budaya Islam, dan asal usul sejarahnya. Penerapan interdisipliner di masa depan dalam studi Islam serta potensi dan manfaatnya dibahas. Dengan mendorong kolaborasi dan kemitraan lintas disiplin, pendekatan interdisipliner dapat menghasilkan pemahaman yang lebih kaya dan kompleks tentang dunia Islam. Studi Islam mendapat manfaat dari strategi interdisipliner karena mendorong pemikiran yang lebih inovatif dan kritis. Kata Kunci: Kajian Islam; studi interdisipliner; pendekatan multidisiplin; Indonesia